2009
DOI: 10.1002/rob.20272
|View full text |Cite
|
Sign up to set email alerts
|

Image‐based path planning for outdoor mobile robots

Abstract: Mobile robots operating in natural terrain need some sort of long-range perception in order to navigate efficiently. Whereas LADAR is a commonly used sensor on such systems, providing range data out to 25 m and beyond, we have instead focused on what information can be extracted from vision. Our robot has only two stereo camera pairs for terrain sensing; they provide reliable stereo data up to 5 m away, but this is not enough to prevent myopic behavior. To overcome this problem, we have developed a novel appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Another approach to the path following problem, that also uses a RGB-D monocular camera, is presented by Huang et al [9]. They combine the range-limited depth information with (long-range) RGB imagery to create cost maps which are subsequently used to plan the robot path.…”
Section: Related Workmentioning
confidence: 99%
“…Another approach to the path following problem, that also uses a RGB-D monocular camera, is presented by Huang et al [9]. They combine the range-limited depth information with (long-range) RGB imagery to create cost maps which are subsequently used to plan the robot path.…”
Section: Related Workmentioning
confidence: 99%
“…Given the irregularities of outdoor locations, terrain classification is an important task in order for the robot to avoid moving away from the path [189]. In [190], the authors present an image-based path planning method for outdoor terrain environments. Moving objects (e.g., animals, pedestrians To cope with all these different challenges (and also to find standard vision-based solutions), general feature-based approaches are commonly used for SLAM, as in [191] and [71], and also for navigation applications [112].…”
Section: Outdoor Locationsmentioning
confidence: 99%
“…(d) Lastly, self-calibration techniques do not use any calibration object and can be considered as 0D approach because only image point correspondences are required. A prototypical paper introduces the widespread application of camera calibration in robot navigation, three-dimensional reconstruction, bio-medicine, virtual reality and visual surveillance [190]. The paper summarizes the methods in different applications, such as traditional calibration, self-calibration and active vision calibration.…”
Section: What Should a Vision System In Gmrs Be Used For?mentioning
confidence: 99%
“…Trials were regularly organized, offering challenging environment in which the robot had to find its way to reach the goal and learn from its experiments. Thus, the different teams involved in the project, such as Bajracharya, Howard, Matthies, Tang, andTurmon (2009), Huang, Ollis, Happold, andStancil (2009), Kim, Sun, Min Oh, Rehg, and Bobick (2006), Konolige et al (2009), Otte, Richardson, Mulligan, and, Procopio, , and Sermanet et al (2009), showed solutions to enable a robot to learn from its experiment and handle unexpected events. Nevertheless, this research is focused on giving an answer to whether the terrain is traversable.…”
Section: State Of the Artmentioning
confidence: 99%